2023
DOI: 10.1088/1748-9326/acdfe8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the SST-precipitation relationship over the Indo-Pacific warm pool under a warming climate

Abstract: The Indo-Pacific warm pool (IPWP) is a region known for its strong atmospheric convection, which plays a key role in global climate. However, in recent decades, the IPWP has experienced human-induced warming, and it has been observed to have a non-linear relationship between Sea Surface Temperature (SST) and precipitation. Despite the rising SSTs, the increase in precipitation is limited until a specific SST, which is defined as saturation threshold SST (STT). The STT indicates a distinct transition before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The sea surface temperature (SST)-atmospheric convection relationship in the Indo-Pacific warm pool (IPWP) is non-monotonic, with studies indicating intensified convection up to a certain SST threshold, beyond which the relationship breaks down. Kim et al (2023) investigate shifts in the SST-precipitation relationship and the SST threshold for deep convection under a warming climate in the IPWP, addressing the gaps in understanding the non-continuous increase in precipitation with SST warming.…”
Section: Tipping Behavior Of the Earth Systemmentioning
confidence: 99%
“…The sea surface temperature (SST)-atmospheric convection relationship in the Indo-Pacific warm pool (IPWP) is non-monotonic, with studies indicating intensified convection up to a certain SST threshold, beyond which the relationship breaks down. Kim et al (2023) investigate shifts in the SST-precipitation relationship and the SST threshold for deep convection under a warming climate in the IPWP, addressing the gaps in understanding the non-continuous increase in precipitation with SST warming.…”
Section: Tipping Behavior Of the Earth Systemmentioning
confidence: 99%
“…Under the background of greenhouse warming, the expansion of surface IPWP and its impacts on global climate has become research hotspots nowadays [20][21][22][23][24][25][26][27] . Recent studies have revealed the warming and expansion of the surface IPWP in uences various climatic phenomena, including the Madden-Julian Oscillation 28,29 , tropical cyclones [30][31][32] , East Asian summer monsoon 33 , El Niño warming 34 , Hadley circulation 35,36 ,Walker circulation 19,24,37 ,Western Paci c subtropical high 38 and extreme precipitation and drought 27,[39][40][41] .…”
Section: Introductionmentioning
confidence: 99%